Women Actors’ Co-Creation in Developing an Ecoikat Mini Collection Based on East Sumba Ikat Textile - Mustikad Zai; Arianti Ina Restiani Hunga; Antik Tri Susanti (Asosiasi Pusat Studi Wanita/Gender & Anak Indonesia (ASWGI), 2026)
Co-creation in heritage-based fashion product development has received increasing scholarly attention, yet the differing positions of women actors in transforming woven textiles remain underexplored. This study examines the co-creation process among women actors in transforming an East Sumba ikat textile into the EcoIkat mini collection. A qualitative case study was conducted at Parahita Craft, Salatiga. Data were collected from December 2025 to July 2026 through participant observation, interviews with five purposively selected informants, and document analysis. The data were analyzed using reflexive thematic analysis and interpreted through Bourdieu's theory of practice. The findings show that different forms of capital were unevenly distributed among the actors, while second-stage evaluation strengthened coordination and the circulation of cultural knowledge. Consumer appreciation, however, did not automatically translate into purchase, indicating that co-creation did not occur on an equal footing because women actors occupied different positions and possessed different forms of capital. These findings suggest that successful heritage-based fashion product development depends on the transmission of cultural knowledge and effective coordination among actors. The study highlights the need for more structured collaboration and transparent benefit-sharing mechanisms.